أثر السياسات المالية والنقدية على ظاهرة الفقر في الجزائر - بوزيني، محمد; دراجي، عيسى (جامعة الوادي University of Eloued, 2025)
This study aims to evaluate the impact of fiscal and monetary policies on poverty in Algeria during the period 1991-2022 using the Autoregressive Distributed Lag (ARDL) model. The analysis focuses on the shortterm and long-term effects of fiscal policy tools based on government spending and tax revenues, as well as monetary policy instruments including exchange rates, interest rates, and money supply. Control variables include unemployment, inflation, trade openness, and economic growth. Key findings indicate that government spending reduces poverty in the short term, while tax revenues and money supply have negligible effects. Exchange rate stability, GDP growth rate, and trade openness alleviate poverty in the long term. Conversely, higher interest rates, unemployment, and inflation exacerbate poverty.
The Impact of Fiscal and Monetary Policies on Poverty in Algeria: An Econometric Study Using the ARDL Model for the Period 1991-2022
مقال
Keywords: الفقر; السياسات النقدية; السياسات المالية; البطالة; التضخم; Poverty; monetary policies; fiscal policies; unemployment; inflation